A Clustering Method for the Extraction of Microcalcifications Using Epipolar Curves in Digital Breast Tomosynthesis - Ho, C; Tromans, C; Schnabel, J; Brady, S (2010)
DBT provides significantly more information than mammography. This offers new opportunities to improve existing microcalcification detection methods. In a companion work in this volume, we showed that the use of epipolar curves can improve both the sensitivity and specificity of microcalcification detection. In this paper, we develop a clustering algorithm to form epipolar curves from candidate microcalcifications (which may be noise points), obtained after applying a detection algorithm to each individual projection. This enables the subsequent 3D analysis for the classification of microcalcification clusters. © 2010 Springer-Verlag.